The Relationship Between Husband's Support and the Intensity of First Stage Labor Pain at the Midwife Umi TPMB, Bekasi - christin jayanti; Yesha Apriyance (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
Increasing education for married couples about the importance of husband support during labor. And providing prenatal counseling programs that involve husbands, so that they are more emotionally and physically prepared to accompany mothers during labor.